Reconstructing air showers with LOFAR using event specific GDAS atmospheres - Mitra, P.; Bonardi, A.; Corstanje, A.; Buitink, S.; Krampah, G. K.; Falcke, H.; Hare, B. M.; Hörandel, J. R.; Huege, T.; Mulrey, K.; Nelles, Anna; Pandya, H.; et al. (Proceedings of Science, 2021)
Estimating the depth of shower maximum Xmax with high precision is of great interest for the study of primary particle composition. One of the systematic uncertainties in reconstructing Xmax from the radio emission of air showers is the limited knowledge of the atmospheric parameters like humidity, pressure, temperature and the index-of refraction. Using the Global Data Assimilation System (GDAS), a global atmospheric model, we have implemented time-dependent realistic atmospheric profiles in the air shower simulation codes CORSIKA and the radio plug-in CoREAS. This program is now available within CORSIKA and flexible to be adapted for different air shower experiments. We have analyzed the LOFAR cosmic ray data with dedicated simulations for each detected air shower with event specific GDAS atmospheres and investigated the effects of pressure and humidity on the reconstructed Xmax. This study shows that for bulk of the events, where the ground pressure is close to US standard atmosphere values, there is a small systematic shift in Xmax that is less than 2 g/cm2 and for very low pressure values the shift is up to 15 g/cm2
CRIS-Team Scopus Importer:2023-08-15